SELF DIRECTED LEARNING WITH VIDEO PROMPTING ON AUTISM SPECTRUM DISORDER STUDENT’S WRITING SKILL - Subroto, Faradila; Hafidz, Moh (Getsempena English Education Journal, 2023)
This research aimed to uncover the implementation of self-directed learning with video prompting on autism spectrum disorder student’s writing skill. This research was conducted on student of SLB Samudra Terra Athena in academic year of 2023-2024. The school located at Masaran village, Tragah, Bangkalan, East Java. The subjects of this research that will be observed by researcher is a student in SMPLB grade at SLB Samudra Terra Athena. The researcher took only 1 student as the subject. A qualitative research approach was employed in this study to describe the current settings in which video prompting is applied to writing skills. The instruments used were field noted observation, interview, and documentation. To draw a conclusion, the data is next examined. The results, self-directed learning with video prompting demonstrates that video prompting can be a useful teaching tool and aid in the practice of writing abilities for students with ASD.